A closed-loop recycling process for carbon fiber-reinforced polymer waste using thermally activated oxide semiconductors: Carbon fiber recycling, characterization and life cycle assessment. (November 2022) - Cheng, Huanbo; Guo, Lijun; Zheng, Lukai; Qian, Zhengchun; Su, Songfei
Highlights: Carbon fiber was recycled using thermally activated of oxide semiconductors. The decomposition rate of resin was 95.5%, and no carbonaceous solid was generated. Compared with landfill and incineration, 8 environmental indicators were reduced. Compared with pyrolysis, 9 environmental indicators were reduced. The energy consumption in recycling was only 23% of that in manufacturing. Abstract: The objective of this study is to investigate the properties of recycled carbon fiber (rCF) and its environmental impact, with a specific focus on the energy consumption of the recycling process based on the use of thermally activated oxide semiconductors (TASC). The mechanical and surface properties of rCF obtained under the optimal process parameters were characterized. The life cycle assessment method was used to evaluate the environmental impact of a closed-loop recycling process for carbon fiber-reinforced polymer (CFRP) waste using TASC. The results indicated that the decomposition rate of resin was 95.5 %, and no carbonaceous solid was generated. The gaseous produced of the recycling process were mainly CO2 and H2 O, and no liquid products were produced. The surface oxidation degree of rCF was relatively slight. COOH was generated on the surface of rCF, which was conducive to improving the interfacial adhesion viscosity with resin. The monofilament tensile strength of rCF was maintained above 97 %. Compared with landfill and incineration, CFRP waste recycling using TASC can make global warming potential, acidification potential and eutrophication potential reduced by 28 %, 32 %, and 25 %, respectively. Ozone layer depletion potential, human toxicity potential and terrestrial ecotoxicity potential in disposing CFRP waste using TASC were 30 %, 21 % and 41 % of that using pyrolysis, respectively. The energy consumption in carbon fiber recycling by TASC was only 23 % of that in virgin carbon fiber manufacturing. TASC is found to be a promising potential strategy for managing CFRP waste.